The Surgeon's Perceived Value of Patient-reported Outcome Measures (PROMs): An Exploratory Qualitative Study of 5 Different Surgical Subspecialties. Issue 3 (9th March 2022) - Mou, Danny; Sisodia, Rachel C.; Castillo-Angeles, Manuel; Ladin, Keren; Bergmark, Regan W.; Pusic, Andrea L.; del Carmen, Marcela G.; Heng, Marilyn
Abstract : Objective: To understand the surgeon's perceived value of PROMs in 5 different surgical subspecialties. Summary of Background Data: PROMs are validated questionnaires that assess the symptoms, function, and quality of life from the patient's perspective. Despite the increasing support for use of PROMs in the literature, there is limited uptake amongst surgeons. Furthermore, there is insufficient understanding of the surgeons' perceived value of PROMs. The aim of this study is to understand how surgeons perceive value in PROMs. Methods: We conducted an exploratory qualitative study to understand the perceived value of PROMs from the perspective of surgeons in various subspecialties. Per convenience sampling, we conducted semi-structured interviews with 30 surgeons from 5 subspecialties across 3 academic medical centers. The surgical subspecialties included bariatric surgery, breast oncologic surgery, orthopedic surgery, plastic and reconstructive surgery, and rhinology. Interviews were transcribed, coded, and evaluated with thematic analysis. Results: Surgeons endorsed that PROMs can be used to enhance clinical management, counsel patients in the preoperative and postoperative settings, and elicit sensitive information from patients that otherwise may go undetected. Obstacles to PROMs use include failure to generate actionable data, implementation obstacles, and inappropriate use of PROMs as a performance metric, with concerns regarding inadequate risk adjustment. Conclusions: Establishing an effective PROMs program requires an understanding of the surgeon's perspective of PROMs. Despite obstacles, different subspecialty surgeons find PROMs to be valuable in different settings, depending on the specialty and clinical context.